Alterations of Colonic Contractility in Long-term Diabetic Rat Model - Kim, Sun Joo; Park, Jae Hyung; Song, Dae Kyu; Park, Kyung Sik; Lee, Jeong Eun; Kim, Eun Soo; Cho, Kwang Bum; Jang, Byoung Kuk; Chung, Woo Jin; Hwang, Jae Seok; Kwon, Joong Goo; Kim, Tae Wan (Journal of neurogastroenterology and motility, 2011)
Dysfunction of the gastrointestinal tract occurs in about 76% of patients who are diabetic for more than 10 years. Although diabetes-related dysfunctions of the stomach such as gastroparesis have been extensively studied over the recent years, studies about the mechanism underlying colonic symptoms in long-term diabetes models are rare. Therefore, the goal of our study was to clarify the nature of colonic dysfunction in a long-term diabetic rat model. The characteristics of colonic smooth muscle were investigated in Otsuka Long-Evans Tokushima Fatty (OLETF) rats, an animal model of type 2 diabetes. These results were compared to those obtained from Long-Evans Tokushima Otsuka (LETO) control rats. Spontaneous contractility of the proximal colon was significantly decreased in the diabetic rats compared to the controls, while the spontaneous contractility of the distal colon was not. The number of interstitial cells of Cajal networks in the proximal colon was greatly decreased in diabetic rats compared to the controls. Contractility of the proximal colon in response to carbachol, an acetylcholine receptor agonist, was significantly weaker in the diabetic rats. In addition, the degree of relaxation in response to nitric oxide in the proximal colon of diabetic rats also appeared to be attenuated. The results from our study suggest that the decrease of interstitial cells of Cajal network, cholinergic receptors, and neuronal nitric oxide synthase in the proximal colon plays important roles in diabetes-related dysfunction of colon.